Fenomena Korean Wave Terhadap Perilaku Belajar pada Siswa Kelas XII IPA di Madrasah Aliyah Negeri 3 Banjarmasin - Harlina; Naza Fatia Firantinur (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2023)
The influence of Korean culture (Korean wave) in Indonesia has recently grown very rapidly. Korean culture that entered Indonesia has anesthetized teenagers in Indonesia. We can see this with the emergence of new trends such as clothing styles, music, spectacle, and lifestyle. This study aims to determine the learning activities of Korean Wave fans and the negative impact of Korean Korean Wave on learning behavior in grade XII students of Science Mandraasah Aliyah Negeri 3 Banjarmasin. The type of approach in this study is field research conducted with qualitative descriptive using a qualitative approach by going into the field directly to explore and examine data related to this research. The informants in this study were 6 students of class XII Science Madrasah Aliyah Negeri 3 Banjarmasin. Data collection techniques are carried out through interviews, observation, and documentation. The results of this study show that, the negative impact of Korean Wave on learning behavior in grade XII students of Science Madrasah Aliyah Negeri 3 Banjarmasin is that they tend to procrastinate in doing assignments and are often negligent in learning time, not infrequently of them often stay up late to watch Korean Wave shows, it makes them often sleepy and not focused when studying in class.